DESIGN APPROVAL REQUEST WORKFLOW APPLICATION NEEDS WORKSHOP ON HSE DEPARTMENT PT . BANGUN SARANA BAJA - Dinanta, Rangga; Puji Widodo, Arifin; Sukmaaji, Anjik (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
HSE (health, safety, environment, dan module and training) department is one of PT bangun Sarana Baja department who support wokshop and company operational. But with the delay in the approval request from the demand for workshops, it creates workshop preparation time is reduced and the incidence of additional costs, such as employee overtime costs and cost penalties from stakeholder (ninecone) in the field. Next issue is the absence of  reports for requirements needs and purchasing needs of all parts of the workshop, it makes the general admin recapitalize back in the form of all the parts at any time if required reporting. Based on these problems, then the author made the application workflow approval requests for workshop needs based on web, where  in this system there is a data input request form, data input purchase form, the allocation needs form and features of approval online to send a notification when there is a demand needs, so as to solve the problem of approval delays that could hamper the process of the workshop. The conclusion on trial results that have been conducted, the application workflow approval requests for workshop needs can be done online, able to generate reports of recapitulation demand needs, the purchase requirement report, allocating demand report  and data recapitulation report from all section.